Genetic and Physiological Responses of Bifidobacterium animalis subsp. lactis to Hydrogen Peroxide Stress - Oberg, Taylor S. (American Society for Microbiology, 2013)
Consumer interest in probiotic bifidobacteria is increasing, but industry efforts to secure high cell viability in foods is undermined by these anaerobes' sensitivity to oxidative stress. To address this limitation, we investigated genetic and physiological responses of two fully sequenced Bifidobacterium animalis subsp. lactis strains, BL-04 and DSM 10140, to hydrogen peroxide (H(2)O(2)) stress. Although the genome sequences for these strains are highly clonal, prior work showed that they differ in both intrinsic and inducible H(2)O(2) resistance. Transcriptome analysis of early-stationary-phase cells exposed to a sublethal H(2)O(2) concentration detected significant (P < 0.05) changes in expression of 138 genes in strain BL-04 after 5 min and 27 genes after 20 min. Surprisingly, no significant changes in gene expression were detected in DSM 10140 at either time. Genomic data suggested that differences in H(2)O(2) stress resistance might be due to a mutation in a BL-04 gene encoding long-chain fatty acid coenzyme A (CoA) ligase. To explore this possibility, membrane fatty acids were isolated and analyzed by gas chromatography-mass spectrometry (GC-MS). Results confirmed that the strains had significantly different lipid profiles: the BL-04 membrane contained higher percentages of C(14:0) and C(16:0) and lower percentages of C(18:1n9). Alteration of the DSM 10140 membrane lipid composition using modified growth medium to more closely mimic that of BL-04 yielded cells that showed increased intrinsic resistance to lethal H(2)O(2) challenge but did not display an inducible H(2)O(2) stress response. The results show that deliberate stress induction or membrane lipid modification can be employed to significantly improve H(2)O(2) resistance in B. animalis subsp. lactis strains.